IbM Kelompok Usaha Tahu Di Kecamatan Lubuk Pakam - Rasita Purba; Elisa Julianti; Kustoro Budiarta; Gamal Kartono (Universitas Negeri Medan, 2014)
Utility of fermented soybean waste has a prospect to become afood product interested by the communityand it is the best alternative that can be offered to the businessmen of fermented soybean. Previously, thewaste is disposed into a river resulting a problem. The waste contains nutrients (protein, carbohydrate,andothers) in which if disposed into a river, they can results in pollution, but if it is managed, it can produceprofitability to the partners of fermented soybean. The goal : design of nata slicer, rate of nata media,production of starter, production of nata de soya, business management and product packaging. Themethod : education, training of production, training of business management, design and advocacy. Thesolution of problem is to provide the material (knowledge) of utility of fermented soybeanwaste, nutritionalcontent, soft skill, manufacture of starter, nata desoya, design of nata slicer in capacity of 6 kgs/30minutes, and application of nata slicer. The resut : slicer of nat de soya, starter product, nata de soyaproduct, packaging and the result of organoleptic test for taste, colorand texture shown a positiveresponse of the partner and participants of IbM. The nata de soya product has received certificate of homeindustry production (SPP-IR T). The analysis of efficiency and economy : previously, the waste is disposedinto a river without benefit (0). After IbM program, in the beginning production, the Partner can produce 6trays of nata de soya (120cups ) with the total capital of Rp. 161.230. The average selling price of natadesoya is of 120 x Rp. 2500 = Rp 300.000. The profitability is of Rp. 138.170. Conclusion : nata de soyaproduct has prospect with a higher cellulose content and it is a newer business for the partner of fermentedsoybean business of the local community that can increase in income and it is an alternative of controllingthe environmental pollution.